2019
DOI: 10.3390/ijerph16040671
|View full text |Cite
|
Sign up to set email alerts
|

Association between Heavy Metals, Bisphenol A, Volatile Organic Compounds and Phthalates and Metabolic Syndrome

Abstract: The incidence of metabolic syndrome (MetS), which causes heart disease and stroke, has increased significantly worldwide. Although many studies have revealed the relationship between heavy metals (cadmium, mercury, and lead), the sum of metabolites of di(2-ethylhexyl) phthalate (DEHP), and MetS, the results remain inconsistent. No study has reported the association between various volatile organic compounds (VOCs) and phthalate metabolites with MetS. This cross-sectional study of a representative sample of adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 54 publications
(72 reference statements)
2
18
0
Order By: Relevance
“…A cross-sectional study using data from the 2012-2014 Korean National Environmental Health Survey II (n 5,251) reported a significant association between urine MEHHP levels and MetS, defined by NCEP ATP III criteria (Shim et al, 2019). In agreement with these results, James-Todd et al, used NHANES data from 2001 to 2010 (n 2,719) and found that higher concentrations of DEHP metabolites, including MEHP, MEHHP, and MEOHP, increased the odds of developing MetS in males (Shim et al, 2019). Similar to findings revealed by Hatch et al, (2008), no correlations were found in adult females.…”
Section: Phthalatesmentioning
confidence: 99%
“…A cross-sectional study using data from the 2012-2014 Korean National Environmental Health Survey II (n 5,251) reported a significant association between urine MEHHP levels and MetS, defined by NCEP ATP III criteria (Shim et al, 2019). In agreement with these results, James-Todd et al, used NHANES data from 2001 to 2010 (n 2,719) and found that higher concentrations of DEHP metabolites, including MEHP, MEHHP, and MEOHP, increased the odds of developing MetS in males (Shim et al, 2019). Similar to findings revealed by Hatch et al, (2008), no correlations were found in adult females.…”
Section: Phthalatesmentioning
confidence: 99%
“…A study from Hong Kong found that short term elevations in atmospheric levels of benzene and TEX (toluene, ethylbenzene, and xylene) was associated with increases in circulatory disease mortality by 5.8% and 3.5% (Ran et al, 2018a), although in a study from Toronto, no intra-urban variations in VOC levels were found be associated with cardiovascular disease mortality (Villeneuve et al, 2013). Other BTEXS such as toluene, styrene, ethylbenzene, and xylenes have been also linked to a higher prevalence of CVD (Xu et al, 2009), and exposure to VOCs such as benzene, ethylbenzene, and styrene have also been found to be associated with higher odds of developing metabolic syndrome (Shim et al, 2019). Along with these data, the results of our study, support the notion that exposure to VOC could have adverse cardiovascular consequences, potentially due to low-level vascular injury reflected by changes in CAC levels.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, Shim et al found a positive association between the concentration of one phthalate metabolite in the urine, MEHHP, and the metabolic syndrome status, involving 5251 participants from the Korean National Environmental Health Survey II (2012-2014), after adjustment for demographic variables. Nevertheless, the authors could not explain the reported association, claiming that chemical properties and health effects of each phthalate metabolite are not well known [178]. Milošević et al analyzed the presence of 10 different phthalate metabolites in the urine samples of 305 participants of both genders (mono-ethyl phthalate (MEP), mono-(2-ethylhexyl) phthalate (MEHP), mono-methyl phthalate (MMP), mono-n-propyl phthalate (MPP), mono-n-butylphthalate (MBP), mono-iso-allyl phthalate (MiAP), mono-nallylphthalate (MnAP), mono-cyclohexyl phthalate (MCHP), MBzP, and mono-n-octyl phthalate (MOP)).…”
Section: Patterns Of Adipose Tissue Distributionmentioning
confidence: 96%